Comparative assessment of serum 8-hydroxydeoxy-guanosine levels among healthy offspring of diabetic and non-diabetic parents - Hasan, Marghoob; Mohieldein, Abdelmarouf Hassan; Almutairi, Fahad Rahib (International Journal of Health Sciences, 2017)
Objective: Parental diabetic status might inherit the likelihood of disease susceptibility. The risk of Type 2 diabetes mellitus is increased among individuals with diabetic parents. Moreover, oxidative stress is thought to be a risk factor in the onset and progression of diabetes. 8-hydroxydeoxy-guanosine (8-OHdG) is widely analyzed biomarker to assess the oxidative DNA damage. We aimed to investigate that serum 8-OHdG level among offspring of diabetic and non-diabetic parents. Materials and Methods: A total of 84 volunteers participated in the study. Questionnaires were applied to record information including demographics, physical activity, smoking, and family history. Blood samples were collected, and laboratory investigations 8-OHdG levels, lipid, and glucose were analyzed using the standard technique. Finally, 24 samples were considered for further analysis. Student’s t-test was applied for statistical analysis. Results: Serum 8-OHdG levels were significantly (P < 0.05) high among healthy offspring of diabetic in comparison of healthy offspring of non-diabetic parents. While nonsignificant differences were found in their body mass index, glucose, and lipid level between the groups. Conclusion: There is possibility of a mild degree of oxidative DNA damage among offspring of diabetic due to family history. Such understanding is essential to avoid other modifiable risk factors related to lifestyle and dietary habit which could possibly control further oxidative stress, to delay the onset of diabetic especially among offspring of diabetic parents.